Biomass-derived carbon electrode materials for supercapacitors - Lu, Hao; Zhao, X. S. (Sustainable energy & fuels, 2017)
This review provides a summary of recent research progress towards biomass-derived carbon electrode materials, including specific cellulose-, lignin- and hemicellulose-derived carbon electrode materials, for supercapacitors. Various lab-scale methods for preparing biomass-derived carbons, including carbonisation and/or activation conditions are discussed. Control over the pore structure, electrical conductivity, and surface functional groups of biomass-derived carbons for enhancing electrocapacitive performance is analysed. Emphasis is made on discussing cellulose-, lignin- and hemicellulose-derived carbon electrode materials for supercapacitor applications. Future research trends in this field are projected.